Implementasi Pendaftaran Nasabah Berbasis Web Pada PT. Bank Rakyat Indonesia Unit Cepoko Ngawi - Choiriyatus Shiddiqiyah; Elly Muningsih (Universitas Bina Sarana Informatika, 2018)
ABSTRACT - Web-based information technology today is needed by the company in facilitating its activities. Likewise with PT. Bank Rakyat Indonesia (BRI) which handles various activities and jobs related to customer service, such as customer registration, savings and loan services, financial installment payment etc. PT. Bank Rakyat Indonesia (BRI) Unit Cepoko is one of the branches of BRI unit that has not used the web in its activities for customer registration service so that this makes it difficult for prospective customers located far from institutions that want to become customers. Therefore it takes a web that can be used to facilitate registration of prospective customers. This study aims to design a web created using Macromedia Dreamweaver 8, where the application is expected to facilitate the implementation of the web for customer registration. Software development using Waterfall method and testing using Black Box Testing method. The results of this study is a webbased information system that allows prospective customers to register as a customer at PT. Bank Rakyat Indonesia (BRI) Unit Cepoko, Ngawi. Keywords: customer registration, web, Waterfall method, Black Box Testing